Real-Time Changes of Heart Rhythm Using MATLAB - Pratama, Destra Andika; Anisah, Masayu; Marlianda, Septi Adila (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Highest mortality from cardiovascular disease (CVD) in 2019: 17.9 million people died worldwide, accounting for 32% of all deaths, 85% of which were due to heart attack and stroke. In Indonesia, 651,481 people die from cardiovascular disease each year, including 331,349 from stroke, 245,343 from coronary heart disease, and 50,620 from hypertension and other cardiovascular diseases. Disturbance of changes in heart rhythm is a condition when the heart's electrical activity is irregular, it can be faster or slower than usual. This disorder is closely related to cardiovascular diseases such as hypertension, heart failure, valvular heart disease, and coronary artery disease. Changes in heart rhythm are usually not dangerous, but if the heartbeat starts to feel abnormal, it can be fatal and cause sudden death. Changes in heart rhythm can be detected using an electrocardiogram, often called an EKG. The function of the EKG is to record information about the state of the heart using electrodes attached to the body. An EKG examination usually has to be done in a hospital to find out the disease the patient is suffering from. This study implements an ECG signal real-time monitoring and processing system using AD8232 sensor module and will display the resulting ECG signal in MATLAB software. This test will be monitored using Simulink MATLAB on the MATLAB R2022b software. Testing the ECG signal studied there were two activities, namely normal activity and after exercising for five minutes. The test was carried out in a sitting position using a 21 years old woman. The results obtained from the system are made using the AD8232 sensor module has been successfully implemented using R peak detection to generate real-time heart rate. It was found that the heart rate varies between 85 to 90 beats per minute during normal activity. Meanwhile, the heart rate after five minutes of exercise reaches 107 to 111 beats per minute. From this heartbeat, we can assume that the heart is functioning normally.